The Oskar Klein memorial lectures - Yang, C. N. (World Scientific, 1991)
This is book should interest a wide audience of readers. The main lectures are good authoritative reviews of the field and are written in a non technical language. Physicists with a broad interest in cosmology and particle theory and also historians of science should find this book useful.